INDIVIDUAL AND ENVIRONMENTAL FACTORS ASSOCIATED WITH ANEMIA KNOWLEDGE AMONG ADOLESCENT GIRLS IN BANDUNG CITY AND REGENCY - tuti surtimanah; Sitti Muhsona Lovia Sousan; Sri Komalaningsih; Metha Dwi Tamara (Kesmas Indonesia, 2026)
Anemia among adolescent girls remains a public health problem that affects growth, cognitive development, and productivity. Adequate knowledge about anemia plays an essential role in its prevention and control. This study aimed to analyze the relationship between individual and environmental characteristics and anemia knowledge among adolescent girls in Bandung City and Regency. A quantitative study with a cross-sectional design was conducted using secondary data from the Hi-Bestie Project 2 involving 1,102 senior high school students. Bivariate analysis was performed using the Chi-Square test, and multivariate analysis was conducted using logistic regression. The results showed that family support, school support, and school location were significantly associated with anemia knowledge (p < 0.05). The most influential factor was family support (OR = 0.26; 95% CI: 0.14–0.50). The study concludes that family and school environments play a crucial role in improving adolescent girls’ knowledge about anemia. Therefore, health promotion programs should actively involve families and educational institutions to strengthen anemia prevention education